Respuesta :

Step-by-step explanation:

a12 = 45 + (12-1)(-6)

= 45-66= -21

Step-by-step explanation:

yes, the other answer is correct.

just to explain a little bit more :

the sequence is clearly built by subtracting 6 from one element to the next.

in other words :

a1 = 45

a n = a n-1 - 6

in such a sequence you do the same operation/ calculation over and over again - once per new element.

the operation in this example is simple - as mentioned : subtract 6.

a1 just gives us a starting value (no operation done for for it) zu, the operation is done one time less than the running number of the element.

therefore, the general element generation algorithm/ formula is :

a n = a1 - (n-1)*6

ACCESS MORE